The Role of Debridement and Spinal Fusion on Frankel Grade, ESR Levels, and CRP in Tuberculosis Spondylitis at Dr. M. Djamil General Hospital, Padang, Indonesia - Ragil Diky Laksmana; Roni Eka Sahputra; Asyumaredha (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: The surgical strategy in the full management of spinal tuberculosis is to debride the tuberculous infection lesion with debridement adequate treatment, reduce symptoms of compression of nerves with adequate decompression, promote the improvement of nerve function, correct kyphosis and prevent deformity, and rebuild spinal stability. This study aims to evaluate the management of debridement and spinal fusion for clinical improvement as assessed by Frankel grade and improvement of laboratory features as assessed by ESR and CRP. Methods: This study is an observational study with a cross-sectional approach which was conducted on 34 research subjects using secondary data. Univariate and bivariate data analysis was conducted to explore the role of debridement and spinal fusion on Frankel grade and ESR and CRP levels. Results: Clinical improvement was seen pre and postoperatively related to Frankel grade. The majority of research subjects experienced improvement based on the Frankel grade. ESR and CRP levels. Conclusion: The action of debridement and spinal fusion plays a role in clinical improvement based on Frankel grade and laboratory improvement based on ESR and CRP values.